Extraction and isolation of alkaloids from the leaves of alseodaphne corneri (Lauraceae) - Jennie, Khoo Hui Chen (N/A, 2015)
Extraction and isolation of alkaloids from the leaves of alseodaphne corneri (Lauraceae) by Jennie, Khoo Hui Chen